HPLC & It’s Utilization in Disease Diagnosis - Ansari, Aadil; Gupta, Ravi; Jhanwar, Mitaksha; Kaushik, Peehu; Sharma, Divyanshu; Khan, Mohd. Shahid; Nagar, Jagdish Chandra (Asian Journal of Pharmaceutical Research and Development, 2020)
High Performance Liquid Chromatography is a technique in analytical chemistry used to separate, identify and quantify each component in a mixture. The HPLC is suitable for a variety of clinical applications, including pharmaceutical development, legal application such as detecting the Presence of illicit drugs in urine & blood. High-performance liquid chromatography is a technique introduced for the accurate diagnosis of hemoglobinopathies, thalassemias & estimation of glycosylated hemoglobin. The advantage of the HPLC system is the excellent resolution, reproducibility & quantification of several normal & abnormal hemoglobin resulting in accurate diagnosis of thalassemia syndromes. HPLC technique which is used to separate the component in across the two equivalents phases i.e. stationary phases is solid or liuqid supported on a solid which is packed into a column while sample moves in along with mobile phase is liuqid or gas. The purpose of this study is to evaluate the HPLC technique in diagnosis of thalassemia syndromes and also correlate it with clinicohematological profile in these cases.